Triple helix analysis from fapemig data for the last 10 years - Crystyane Ferreira Bernardino; Joseane Viola Debortoli; Washington Gonçalo Rodrigues Veloso; Adriana Gontijo Nunes; Lilian Bambirra de Assis (Innovation & Management Review, 2020)
Purpose - The puropose of this study is to analyze the functioning of the triple helix interaction in Minas Gerais, through the case study of the Minas Gerais State Research Support Foundation (Fapemig). Design/methodology/approach The information was collected from the Activity Reports published by Fapemig. Quantitative methods were used for structural analysis and data tabulation of the researched and qualitative programs for a procedural and documentary analysis of projects promoted by Fapemig between the years 2009 and 2018. Findings The Fapemig showed itself to be a fundamental agent for innovation and the development of interactions between the state, universities and companies in Minas Gerais, through the creation of programs, offered in public notices, financing them and creating a space of consensus among the agents. Originality/value There is few research on triple helix interaction for the state of Minas Gerais; most research on this topic is concentrated in some regions of the country, and the present work contributes to fill this research gap, besides demonstrating, in a case study, applications of recent and still little-explored concepts of the literature on triple helix.
Keywords: 650; Fapemig; Minas Gerais; Triple helix